1974
DOI: 10.1021/ja00831a001
|View full text |Cite
|
Sign up to set email alerts
|

Hydration of ions in dipolar aprotic solvents

Abstract: Interactions between water at low concentrations and 1:l electrolytes have been studied in four dipolar aprotic solvents of increasing basicity: sulfolane (TMS) < acetonitrile (AN) < propylene carbonate (PC) << dimethyl sulfoxide (DMSO). The experimental methods used involved solubility, proton nmr, vapor pressure, and calorimetric determinations. Results are interpreted in terms of hydration constants K1 and enthalpies Ail1 for the 1:l complexes with CI-, NO3-, H+, Li+, Na+, and Ag+ ions in most of the cited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1975
1975
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…For example, in phase transfer catalysis, water molecules may accompany the transfer of an ionic reactant from water to the organic phase and thus significantly affect its reactivity [1]. Several experiments such as UV-vis [2], proton NMR [3][4][5][6], and IR [7] have confirmed that some water molecules are coextracted when reagents such as tetraphenylborate are used to extract hydrophilic inorganic ions from water to nitrobenzene. Accurate numbers of the co-extracted water molecules per ion have been established in nitrobenzene [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in phase transfer catalysis, water molecules may accompany the transfer of an ionic reactant from water to the organic phase and thus significantly affect its reactivity [1]. Several experiments such as UV-vis [2], proton NMR [3][4][5][6], and IR [7] have confirmed that some water molecules are coextracted when reagents such as tetraphenylborate are used to extract hydrophilic inorganic ions from water to nitrobenzene. Accurate numbers of the co-extracted water molecules per ion have been established in nitrobenzene [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Having established that monomeric species predominate for both acid and water (at low water concentrations), we of Huyskens and co-worker (20), in acetonitrile, were able to interpret our vapor pressure results suggest that H 2 0 behaves as a H-bond acceptor in terms of the association reaction weaker than C1-and also Br-. The low "basicity" of isolated H 2 0 molecules compared with the high basicity of bulk water has already The water vapor pressure curves shown in been remarked upon (22,6). Our observed low Fig.…”
Section: Hydration Constants Of the Acidsmentioning
confidence: 57%
“…Our hydration constants K, for methanesulfonic, picric, and 3,5-dinitrobenzoic acids in Sulfolane are not too different from, but somewhat lower than the same constants K, in acetonitrile, which are respectively 14, 0.5, and 1.8 (3). This difference may result from slightly weaker interactions of the acids with acetonitrile than with Sulfolane since water interactions with both solvents are similar (6). However, in a more recent study Kolthoff and Chantooni concluded from near infrared measurements that picric acid is not hydrated in acetonitrile (7).…”
Section: Hydration Constants Of the Acidsmentioning
confidence: 97%
“…The treatment for obtaining values of the 1:1 complex formation constant K and complex shift S¡ is essentially as described earlier. 9 Our results for sulfolane together with values for AN are given in Table I. The highest values of K are somewhat ap- proximate since the curvature of the plots ofvs.…”
Section: Resultsmentioning
confidence: 77%